Prevalence and socio-demographic correlates of poor sleep quality among older adults in Hebei province, China - Yun-Shu Zhang (Nature Portfolio, 2020)
Abstract Poor sleep quality is associated with negative health outcomes and high treatment burden. This study investigated the prevalence of poor sleep quality and its socio-demographic correlates among older adults in Hebei province, which is a predominantly agricultural region of China. A large-scale cross-sectional epidemiological survey was conducted from April to August 2016. The study used a multistage, stratified, cluster random sampling method. Sleep quality was assessed by the Pittsburgh Sleep Quality Index (PSQI). A total of 3,911 participants were included. The prevalence of poor sleep quality (defined as PSQI > 7) was 21.0% (95% CI 19.7–22.2%), with 22.3% (95% CI 20.9–23.8%) in rural areas and 15.9% (95% CI 13.4–18.4%) in urban areas. Multivariable logistic regression analyses found that female gender (P < 0.001, OR 2.4, 95% CI 2.00–2.82), rural areas (P = 0.002, OR 1.5, 95% CI 1.14–1.86), presence of major medical conditions (P < 0.001, OR 2.4, 95% CI 2.02–2.96) and family history of psychiatric disorders (P < 0.001, OR 2.7, 95% CI 1.60–4.39) were independently associated with higher risk of poor sleep quality. Poor sleep quality was common among older adults in Hebei province of China. Regular assessment of sleep quality and accessible sleep treatments for older population should be provided in agricultural areas of China.